Pengembangan Media Pembelajaran Berbasis Flip-Book digital Pada Subtema “Aku Anak Mandiri” di Kelas 3 Sekolah Dasar - Nopian, Mohammad Anggi; Ismatullah, Ismatullah; Dayurni, Popi (Journal of Professional Elementary Education, 2025)
This research is motivated by the low use of digital learning media at SDN Ketileng 1, especially in thematic learning for grade III. Teachers tend to use lecture methods and textbooks, which cause students to be less active and get bored quickly. To overcome this, a digital Flip-Book-based learning media was developed on Theme 8 Subtheme 2 "I am an Independent Child". The research method used is Research and Development (R&D) according to Sugiyono, modified into six stages: problem analysis, data collection, product design, design validation, design revision, and product trial. The digital Flip-Book media developed includes PPKn, Indonesian, and Mathematics materials, adjusted to Basic Competencies and learning indicators. The validation results by media experts showed an average feasibility of 75.95%, while validation by material experts reached an average of 84.6%, both of which are in the "Feasible" to "Very Feasible" categories. Limited trials on grade III students resulted in a positive response with a percentage of 86.88%, indicating that this media is very good for use in learning. Thus, this digital Flip-Book effectively increases student engagement and understanding in thematic learning